y(y + 4) - y = 6 is a quadratic equation. True False

Original conversation

User: y(y + 4) - y = 6 is a quadratic equation.
True
False

Weegy: False.
y(y 4) - y = 6 is written as:
y^5 -y - 6 = 0.
A quadratic equation is a second-order polynomial equation in a single variable y and this is not a second order polynomial equation.
befeeter|Points 406|

The length of a rectangle is 3 more than twice the width. The area of the rectangle is 119 square inches. If x = the width of the rectangle, the equation that can be used to solve this problem is: 2x^2 + 3x - 119 = 0. Width is x, the length should be: 2x + 3 The area = width x length = x(2x + 3) = 119 Rearrange the equation: 2x^2 + 3x - 119 = 0

Added 4/3/2014 9:09:59 PM

This answer has been confirmed as correct and helpful.

There are no comments.